MODEL BIAYA OPERASIONAL KENDARAAN SEPEDA MOTOR MENGGUNAKAN ANALISIS REGRESI LINIER BERGANDA - Veranita Veranita (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2017)
Need for policies and activities such as housekeeping activities and policy development inorder to maintain the order and comfort to reduce the problems of the city in the future.Based on the context of the analysis and evaluation purposes traffic congestion costs, caused by an increase in the number of motorcycle users against traffic and transport in urban  areas, it is  first necessary  to  understand  the Vehicle  Operating  Costs (VOC) motorcycles  in  greater  depth.  In  this  reseaarches  conducted  interviews  done  with  a special kind of motorcycle scooter matic domiciled in Dormitory Military Makorem 012 / TU Alue Peunyareng  route from the hostel  to  the Central Business  District  (CBD). Analysis of the data for the calculation of the BOK is done manually and statistical analysis using SPSS (Statistical Product and Service Solution) version 20. Statistical analysis includes analysis of the correlation coefficient, multiple linear regression, coefficient of determination (R2), t test and F to variable bound (dependent) is traveling, and the independent variable (independent), namely fuel, engine oil, gear oil, tires, tires, servicing, spares and unexpected costs. The results were obtained magnitude maximum BOK matic scooter type motorcycle with a capacity of 150 CC, 125 CC, 115 CC, 110 CC, respectively, are the costs Rp 379.10 / km, Rp667,44 / km, Rp749,32 / km and Rp552,96 / km. While the average BOK is Rp327,34  / km, Rp365,30  / km, Rp471,80 / km and Rp332,11 / km. The factors that affect the BOK is the cost of fuel oil (BBM), the cost of engine oil, servicing fees, and the cost of spare parts, with a probability level of significance of less than 0.05 (5%). BOK Model matic scooter type motorcycle, which is Y= 104.325 + 0.006 X1 + 0,003X2 - 0,002X6 + 0,000X7. Keywords : Model, BOK, Motorcycles, Multiple Linear Regression